P72 Is the use of a novel high frequency airway oscillating device feasible for the management of chronic obstructive pulmonary disease?. (15th November 2017) - Daynes, E; Harvey-Dunstan, TC; Greening, NJ; Singh, SJ
Abstract : Introduction and Objectives: Chronic Obstructive Pulmonary Disease (COPD) is characterised by expiratory flow limitation contributing to dyspnoea and impacting on exercise capacity and quality of life. Inspiratory muscle training is commonly used to improve inspiratory muscle strength and endurance, exercise capacity and quality of life. The High Frequency Airway Oscillating (HFAO) device uses flow resistance to provide combined inspiratory and expiratory muscle training. It is hypothesised that the use of a HFAO device may improve the strength of the respiratory muscles resulting in reduced sensation of dyspnoea. This study was designed to explore the feasibility of HFAO in COPD. Methods: Patients with symptomatic COPD were included (MRC of ≥3). This was a single arm feasibility study using a HFAO device. All participants used the device for 5 min, 3 times per day, for eight-weeks. The primary outcomes were recruitment, attrition and compliance. Self-reported daily diaries identified participants as adherent if they completed ≥75% of device use. Secondary outcome measures included maximal inspiratory and expiratory pressures (Pimax /Pemax ), Incremental and Endurance Shuttle Walking Tests (ISWT/ESWT) and health related quality of life questionnaires. Data was analysed by a Wilcoxon Signed Rank test and considered statistically significant if p<0.05. Results: 23 participants with COPD were recruited (65% male, mean [SD] age 65[5] years, FEV1 %predicted 44[16], FEV1/FVC ratio 0.46 [0.13]), median [IQR] MRC 4 [3–5], of which 20 participants completed the intervention. 62% of potential participants were recruited and there was an attrition rate of 13%. 90% of participants were considered adherent to device use. A significant improvement in MRC score (median change −1 [IQR 3–3]) was observed (p≥0.01). Significant improvements were seen in Pimax and Pemax (table 1 ). Pre and post intervention exercise performance and quality of life are shown in Table 1. Conclusions: This shows promising Results in the use of HFAO to reduce dyspnoea within COPD. Recruitment and attrition was appropriate and compliance rates were considered suitable and therefore it is feasible to proceed to a randomised controlled trial.